2015
DOI: 10.1002/jeab.136
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of visual-visual conditional discriminations

Abstract: We assessed the emergence of visual-visual conditional discriminations following training of vocal tact and intraverbal relations. Ten preschool-age children learned to vocally tact six visual stimuli, A1 through B3. Next, they learned to respond intraverbally to the dictated names of A1, A2, and A3 by vocalizing the names of B1, B2, and B3, respectively. Emergent A-B and B-A relations were tested in a visual-visual match-to-sample (MTS) task. Five of ten participants passed the test, with or without a prompt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 39 publications
4
40
1
Order By: Relevance
“…Additionally, all participants emitted experimentally defined or self-generated tacts and intraverbals at some point during MTS tests. Thus, differently from Petursdottir et al (2015), whose participants included children between 3.5 and 5.5 years old, our results show that at least under our experimental preparation, college students' responses during symmetry matching tasks seems dependent upon the emission of B'A' Bsymmetrical^intraverbals.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Additionally, all participants emitted experimentally defined or self-generated tacts and intraverbals at some point during MTS tests. Thus, differently from Petursdottir et al (2015), whose participants included children between 3.5 and 5.5 years old, our results show that at least under our experimental preparation, college students' responses during symmetry matching tasks seems dependent upon the emission of B'A' Bsymmetrical^intraverbals.…”
Section: Discussioncontrasting
confidence: 61%
“…In an attempt to directly manipulate intraverbal naming to produce matching performances, Petursdottir et al (2015) evaluated whether AB and BA (symmetry) conditional discriminations would emerge after A'B' intraverbal training. In other words, experimenters trained participants to tact arbitrary pictures with individual names (e.g., BPsi^and BKibi^) and to relate these names in intraverbal frames (e.g., BPsi goes with Kibi^).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These previous experiments (Ma et al, ; Petursdottir et al, ; Santos et al, ) have yielded significant outcomes for both stimulus equivalence and verbal behavior research. In one experiment with young children, researchers found failures to establish conditional discriminations and results that were inconsistent (Petursdottir et al, ) with the bidirectional naming hypothesis (Horne & Lowe, ). The other two studies (Ma et al, ; Santos et al, ), using verbally sophisticated participants, demonstrated emergence of novel intraverbals and the formation of equivalence classes.…”
mentioning
confidence: 94%
“…Equivalence classes may not only be established by teaching common names to dissimilar stimuli (common bidirectional naming, C‐BiN), but also by teaching intraverbal relations among them (intraverbal bidirectional naming, I‐BiN). When stimuli are linked together through intraverbal training, such as “Cardinal goes with Virginia”, and “Virginia goes with dogwood,” participants may learn to treat them as members of the same equivalence class, as measured by both selection (i.e., MTS) and vocal (i.e., intraverbal) tests (e.g., Ma, Miguel, & Jennings, ; Petursdottir, Carp, Peterson, & Lepper, ; Santos, Ma, & Miguel, ). Thus, during MTS tests, participants may tact the sample (e.g., saying, “Dogwood”), the product of which would evoke an intraverbal (“Dogwood goes with Virginia.”), whose product would serve as a discriminative stimulus (S D ) for the selection of the correct comparison.…”
mentioning
confidence: 99%